The impact of dementia and extremity injuries on the plasticity of long-term care demand: An analysis of counterfactual projection scenarios based on German health insurance routine data - Alexander Barth (Comparative Population Studies (CPoS), 2019)
Although demand for long-term care (LTC) in Germany is expected to increase over the coming decades, the LTC sector will struggle to provide sufficient capacity. Evaluating the impact of different risk factors on future LTC demand is necessary in order to make informed policy decisions. With regard to LTC need, dementia and lower extremity injuries (LEI) are common risk factors. Both are used to demonstrate their maximum attainable efficacy in mitigating the future increase in overall LTC need, both at home and in nursing homes. We use a multi-state projection model for which the estimation of the underlying transition and mortality rates is based on longitudinal health claims data from AOK, Germany's largest public health insurance provider, between 2004 and 2010. We project six different scenarios of LTC for ages 75+ in Germany for the period from 2014 to 2044, including counterfactual scenarios that remove the effects of LEI, dementia, or both. Our multi-state projections distinguish between home-based and institutional LTC. Removing the effect of LTC risk factors mitigates the increase in total LTC demand and postpones demand until a later age. Removing dementia markedly shifts future care demand from institutional LTC to LTC at home and even increases demand for LTC at home at older ages beyond the baseline projection due to the dual function of dementia as a risk factor for both LTC demand and mortality. Removing LEI has less of an effect on overall and sectoral LTC demand. Removing both risk factors at the same time results in the greatest impact, which is even more marked than that of both individual scenarios combined, thus indicating a synergistic relationship between dementia and LEI on LTC risk. The type of LTC demand (home-based or institutional) shows considerable plasticity when specific risk factors are removed. We demonstrate the degree to which LTC demand can be affected in favour of LTC at home, using dementia and LEI as examples of potentially modifiable risk factors, and thus show how the efficacy of potential intervention targets for policy-makers can be assessed. This study provides evidence on the degree of plasticity of future long-term care demand at home and in institutions that would hypothetically be attainable when completely removing specific cognitive or physical risk factors of care need (dementia or lower EI). It is based on large-scale health claims data, which contain longitudinal individual level data on morbidity and long-term care status. A close link exists between the cognitive risk factor of dementia and the type of LTC, as its absence shifts care demand to home-based care at older ages. The study also demonstrates the usefulness of counterfactual projections based on health claims data in assessing the hypothetical maximum efficacy of different intervention strategies.
urn:nbn:de:bib-cpos-2019-19en5
Keywords: 300; Long-term care; Counterfactual projections; Dementia; Extremity injuries